Effects of technological changes on China's carbon emissions - Chen, Jiandong; Gao, Ming; Mangla, Sachin Kumar; Song, Malin; Wen, Jie (Technological forecasting & social change, 2020)
•The opposing effects of technological changes on CO2 emissions in China studied.•The LMDI and Solow models were combined to analyze the emission data.•The relationship between technological progress and CO2 emission is complex.•Technological progress reduced China's overall CO2 emissions (2005–2015).•We propose policies based on our conclusions for further reducing CO2 emissions. Technological progress is widely recognized as a method of reducing carbon emissions. However, many studies have shown that it can also lead to increased energy consumption and carbon emissions. To study the effects of technological changes on carbon emissions, we decomposed technological changes into environmental technological changes and production technological changes. Furthermore, we analyzed the effects of technological progress on carbon emissions by embedding the Solow residual model into the logarithmic mean Divisia index model. We used data from China's 30 provinces to calculate the regional effects of technological progress during 2005–2015. We drew the following conclusions: 1) China's overall domestic technological progress reduced carbon emissions over the study period; 2) technological progress in Central and West China significantly reduced carbon emissions, whereas that in East China slightly increased emissions; and 3) the relationship between technological progress and carbon emissions is complex and depends on both environmental technological changes and production technological changes.